2019
DOI: 10.7150/jca.30663
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of aspartate aminotransferase to lymphocyte ratio and systemic immune-inflammation index for Overall Survival of Hepatocellular Carcinoma Patients Treated with palliative Treatments

Abstract: Background : Lymphocytes were reported to play a significant part in host anticancer immune responses and influence tumour prognosis. Few studies have focused on the prognostic values of aspartate aminotransferase (AST) to lymphocyte ratio (ALRI), aspartate aminotransferase to platelet count ratio index (APRI) and systemic immune-inflammation index (SII) in hepatocellular carcinoma (HCC) treated with palliative treatments. Methods : Five hundred and ninety-eight HCC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…However, beyond these markers, which calculate only two immune cells, a novel index, SII, is based on three peripheral blood cells, including platelet, neutrophil, and lymphocyte. SII has been reported to be a more objective index with better predictive reliability for prognosis, reflecting the host immune status more comprehensively in various types of cancers [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…However, beyond these markers, which calculate only two immune cells, a novel index, SII, is based on three peripheral blood cells, including platelet, neutrophil, and lymphocyte. SII has been reported to be a more objective index with better predictive reliability for prognosis, reflecting the host immune status more comprehensively in various types of cancers [18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that tumors are associated to systemic inflammation. [27][28][29] However, the mechanisms between tumors and inflammation reaction are yet ambiguous and poorly understood. Some studies have suggested that systemic inflammatory cells, such as neutrophils, monocytes, platelets, and lymphocytes, are linked to prognosis of many malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Ascites are the most common rst symptom of liver decompensation, which seriously affects the prognosis of patients with cirrhosis (13). The ascites were evaluated to be independent risk factor for the survival of HCC patients, and has been incorporated into several HCCrelated risk models (13,14,16,18). Therefore there might be an over-simpli cation in the ALBI grade, and the ascites could be retained as the parameters for the assessing of the liver function.…”
Section: Resultsmentioning
confidence: 99%
“…And the ascites always predicted the prognosis more accurately than the albumin level in previous HCC related risk models. Additionally, the ascites have been incorporated into several HCC-related prognostic model (such as HCC with portal vein tumor thrombus, HCC after ablation, HCC after palliative treatments, and BCLC stage C HCC) (14)(15)(16)(17)(18). Therefore it appears arbitrary and crude that eliminating the ascites variable from the risk prediction model for BCLC stage B HCC patients.…”
Section: Introductionmentioning
confidence: 99%